Preparation method of cadmium-naphthalimide photochromic material
By preparing cadmium-naphthalimide-based photochromic materials and fabricating test strips, the problems of expensive and complex amine detection equipment have been solved, enabling rapid and visualized detection of amine substances.
Patent Information
- Application Number
- CN202511530241.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-10-24
- Publication Date
- 2026-01-06
AI Technical Summary
Existing amine detection technologies and equipment are expensive, complex to operate, and difficult to achieve rapid on-site visual detection.
A method for preparing cadmium-naphthalimide-based photochromic materials was adopted. Cadmium-naphthalimide-based photochromic materials were synthesized by a solvothermal method and then prepared into amine-based test strips. The color change was detected by stimulating light.
It achieves highly sensitive, rapid, and reversible detection of amine substances, simplifies the detection process, reduces costs, and meets the needs of on-site emergency testing.
Smart Images

Figure CN121270945A_ABST
Abstract
Description
Technical Field
[0001] This invention relates to the field of metal-organic framework photosensitive materials technology, specifically a method for preparing a cadmium-naphthalimide-based photochromic material. Background Technology
[0002] With the increasing demand for smart materials in modern technology, photochromic materials, due to their ability to undergo reversible color changes under light stimulation, have shown great application potential in numerous fields. Metal-organic frameworks (MOFs) are a class of crystalline materials with periodic network structures constructed by the self-assembly of metal ions or metal clusters and multidentate organic ligands through coordination bonds. Due to their advantages such as ultra-high specific surface area, high and tunable porosity, diverse structural compositions, open metal sites, and chemical modifiability, they show promising application prospects in gas storage and separation, pollutant adsorption, fluorescence sensing, catalysis, supercapacitors, medicine, and sterilization and algae removal.
[0003] Amines have wide applications and distribution in many fields such as chemical engineering, pharmaceuticals, and environmental monitoring. However, some amine compounds are toxic and volatile, posing potential hazards to human health and the environment. Current methods for detecting amines, such as gas chromatography and liquid chromatography, while highly accurate, suffer from drawbacks including expensive equipment, complex operation, the need for specialized personnel, and time-consuming testing, making them unsuitable for rapid on-site detection. Therefore, there is a need to develop a simple, rapid, sensitive, and low-cost cadmium-naphthalimide-based photochromic material to achieve visualized detection of amines. Summary of the Invention
[0004] To address the shortcomings of existing technologies, this invention provides a method for preparing cadmium-naphthalimide-based photochromic materials, which possesses advantages such as high sensitivity, excellent selectivity, good reversibility and repeatability, stable physicochemical properties, and extremely fast photoresponse capability. This method solves the problems of expensive equipment, complex operation, long detection cycle, and difficulty in achieving rapid on-site visualization detection in existing amine substance detection technologies.
[0005] To achieve the above objectives, the present invention provides the following technical solution: a method for preparing a cadmium-naphthalimide-based photochromic material, comprising the following steps: S1. Cadmium salt, naphthalimide ligand (N,N'-bis(4-pyridinylmethylene)-1,4,5,8-naphthalimide) and thiophene-2,5-dicarboxylic acid ligand are dissolved in a mixed solvent of deionized water and N,N-dimethylformamide according to a set molar ratio, and the mixture is stirred to obtain mixture A. S2. Place the dissolved mixture A in a reaction vessel with a polytetrafluoroethylene liner and carry out the synthesis reaction by solvothermal method. After the reaction is completed, cool to room temperature at a rate of 3.5-4.0℃ / h. Wash with deionized water 3-5 times until the supernatant is colorless and neutral. Finally, orange-yellow block crystals are obtained, which are cadmium-naphthalimide-based photochromic materials. S3. Preparation of amine test strips: Using filter paper as the bottom layer, cadmium-naphthalimide-based photochromic material, dispersant and binder are mixed in sequence and filtered onto the filter paper to obtain amine test strips.
[0006] Preferably, in step S1, the molar ratio of cadmium salt and naphthalimide ligand (N,N'-bis(4-pyridimethylene)-1,4,5,8-naphthalimide) to thiophene-2,5-dicarboxylic acid ligand is (1-2):1:1; the cadmium salt is selected from any one of cadmium nitrate, cadmium chloride, or cadmium bromide.
[0007] Preferably, in step S1, the volume ratio of deionized water to N,N-dimethylformamide is (1-4):1.
[0008] Preferably, the specific process for obtaining mixture A in S1 is as follows: stirring at room temperature and a speed of 700-800 rpm for 2-3 hours, and then filtering through a 0.22 μm organic filter membrane to obtain mixture A.
[0009] Preferably, the synthesis reaction conditions in S2 are: constant temperature at 90-110℃ for 2-4 days.
[0010] Preferably, the preparation of the amine test paper in S3 is as follows: using filter paper as the bottom layer, the cadmium-naphthalimide-based photochromic material, dispersant, and binder prepared in S2 are mixed in a mixed solvent of methanol and ethanol in a certain proportion to form a uniform mixed solution. Then, the mixed solution is filtered onto the filter paper, and its loading is controlled at 49.5-50.5 mg / cm². After drying, the amine test paper is obtained.
[0011] Preferably, the photochromic material has the structural formula [Cd(DPMNI)(H2TDC)]. n Its molecular formula is C 32 H 18 CdN4O8S; wherein, DPMNI is a naphthalimide ligand (N,N'-bis(4-pyridimethylene)-1,4,5,8-naphthalimide), and H2TDC is a thiophene-2,5-dicarboxylic acid ligand; The asymmetric unit consists of a cadmium atom, half of a naphthalimide ligand, half of a thiophene-2,5-dicarboxylic acid ligand, a nitrogen atom derived from the naphthalimide ligand, and two oxygen atoms derived from the thiophene-2,5-dicarboxylic acid ligand. The cadmium atom at the metal center has a six-coordinate octahedral geometry. Two nitrogen atoms are derived from two different naphthalimide ligands and four oxygen atoms are derived from two different thiophene-2,5-dicarboxylic acid ligands. Due to the presence of coordination sites for nitrogen atoms and carboxylate ions in the naphthalimide ligands and thiophene-2,5-dicarboxylic acid ligands, which are connected to the cadmium atom at the metal center, and the intermolecular interactions, the structure of this material can form a three-dimensional network structure with pores.
[0012] Preferably, the photochromic material is crystallized in the orthorhombic crystal system of space group Pnma, with a cell parameter of a = 23.259(4) Å. b =10.2229(17)Å, c =12.294(2)Å, α = β = γ = 90°, V =2923.3(8) Å 3 , Z =4.
[0013] Preferably, the photochromic material changes color from orange-yellow to brown after 5-6 seconds of light exposure, and can be restored to its original color after heating at 118-120℃ for 1-1.1 hours, and the color change process is reversible.
[0014] Preferably, the photochromic material is used in the field of amine test strips.
[0015] Compared with the prior art, the present invention provides a method for preparing cadmium-naphthalimide-based photochromic materials, which has the following beneficial effects: 1. The preparation method of this invention is simple, using a solvothermal synthesis method, and no toxic substances are generated during the entire process, while requiring no special equipment.
[0016] 2. The cadmium-naphthalimide-based photochromic material prepared by this invention has extremely fast photoresponse capability. Under visible or ultraviolet light irradiation, it can change from orange-yellow to brown within 5 seconds, turn brown within 1 minute, and reach saturation to dark brown within 2 minutes. Due to the special three-dimensional network structure of the material, its color can be maintained for 30 days after light irradiation and can be restored to its original color by heating at 120°C for 1 hour.
[0017] 3. The cadmium-naphthalimide-based photochromic material prepared by the method of this invention can undergo a significant color change in a very short time after contacting amine substances. It can not only provide immediate feedback on the detection results, but also be made into filter paper for visual detection of amine substances, thereby greatly improving the detection efficiency and ultimately meeting various on-site emergency detection needs. Attached Figure Description
[0018] Figure 1 This is a crystal structure diagram of the material in Example 1 of the present invention; Figure 2 This is a crystal packing diagram of the material in Embodiment 1 of the present invention; Figure 3 These are photographs and ultraviolet solid diffuse reflectance images of the material in Example 1 of this invention under different lighting times; Figure 4 The X-ray powder diffraction (XRD) patterns of the material before and after illumination in Example 1 of this invention are shown. Figure 5 Thermogravimetric analysis (TGA) of the material in Example 1 of this invention; Figure 6 The electron paramagnetic resonance (EPR) spectra of the material before and after illumination in Example 1 of this invention are shown below. Figure 7 This is a color change diagram of the material in Embodiment 1 of the present invention as a function of light exposure time; Figure 8 This is a color change diagram of the adsorption of amines by the material in Example 1 of the present invention; Figure 9 The color change diagram of the test strip made from the material in Example 1 of this invention for detecting amine substances; Figure 10 This is an ultraviolet diffuse reflectance image of the material in Example 1 of the present invention showing the adsorption and color change of amines. Figure 11 This is the X-ray powder diffraction (XRD) pattern of the material in Example 1 of the present invention for amine substances. Detailed Implementation
[0019] The technical solutions of the embodiments of the present invention will be clearly and completely described below with reference to the accompanying drawings. Obviously, the described embodiments are only some embodiments of the present invention, and not all embodiments. Based on the embodiments of the present invention, all other embodiments obtained by those skilled in the art without creative effort are within the scope of protection of the present invention.
[0020] Please see Figures 1-11 A method for preparing a cadmium-naphthalimide-based photochromic material includes the following steps: S1. Cadmium salt, naphthalimide ligand (N,N'-bis(4-pyridinylmethylene)-1,4,5,8-naphthalimide) and thiophene-2,5-dicarboxylic acid ligand are dissolved in a mixed solvent of deionized water and N,N-dimethylformamide according to a set molar ratio, and the mixture is stirred to obtain mixture A. S2. Place the dissolved mixture A in a reaction vessel with a polytetrafluoroethylene liner and carry out the synthesis reaction by solvothermal method. After the reaction is completed, slowly cool to room temperature at a rate of 3.5-4.0℃ / h. Wash with deionized water 3-5 times until the supernatant is colorless and neutral. Finally, orange-yellow block crystals are obtained, which are cadmium-naphthalimide-based photochromic materials. S3. Preparation of amine test strips: Using filter paper as the bottom layer, cadmium-naphthalimide-based photochromic material, dispersant and binder are mixed in sequence and filtered onto the filter paper to obtain amine test strips.
[0021] The structural formula of the cadmium-naphthalimide-based photochromic material prepared from the above S1-S3 is [Cd(DPMNI)(H2TDC)]. n Its molecular formula is C 32 H 18 CdN4O8S has the following specific composition: (1) DPMNI is a naphthalimide ligand (N,N'-bis(4-pyridimethylene)-1,4,5,8-naphthalimide), and H2TDC is a thiophene-2,5-dicarboxylic acid ligand; (2) The asymmetric unit consists of a cadmium atom, half of the naphthalimide ligand, half of the thiophene-2,5-dicarboxylic acid ligand, and a nitrogen atom derived from the naphthalimide ligand and two oxygen atoms derived from the thiophene-2,5-dicarboxylic acid ligand; (3) The cadmium atom at the metal center has a six-coordinate octahedral geometry. Two nitrogen atoms are derived from two different naphthalimide ligands and four oxygen atoms are derived from two different thiophene-2,5-dicarboxylic acid ligands. Due to the presence of nitrogen atoms and carboxylic acid ion coordination sites in the naphthalimide ligands and thiophene-2,5-dicarboxylic acid ligands, which are connected to the cadmium atom at the metal center, as well as the intermolecular interactions, the structure of this material can form a three-dimensional network structure with pores.
[0022] (4) The photochromic material crystallizes in the Pnma space group of the orthorhombic crystal system, and its unit cell parameter is a = 23.259(4) Å. b =10.2229(17)Å, c =12.294(2)Å, α = β = γ = 90°, V=2923.3(8) Å 3 , Z =4.
[0023] Specifically, the cadmium salt in S1 is selected from any one of cadmium nitrate, cadmium chloride, or cadmium bromide; Specifically, the molar ratio of cadmium salt and N,N'-bis(4-pyridinylmethylene)-1,4,5,8-naphthodiimide and thiophene-2,5-dicarboxylic acid ligand in S1 is (1-2):1:1.
[0024] Specifically, in the solvothermal synthesis experiment of S1 cadmium-naphthalimide-based photochromic material, when the molar ratio of cadmium salt to N,N'-bis(4-pyridimyl)-1,4,5,8-naphthalimide and thiophene-2,5-dicarboxylic acid ligand is outside the range of 2:1:1, the synthesized cadmium-naphthalimide-based photochromic material has low purity and many impurities, so it is not used. Therefore, controlling the molar ratio of the three reagents within the reasonable range of (1-2):1:1 in this experiment can avoid the decrease in material purity and the increase in impurity content due to deviation of the ratio, so as to ensure the synthesis quality of the target photochromic material.
[0025] Specifically, the volume ratio of deionized water to N,N-dimethylformamide solution in S1 is (1-4):1.
[0026] Specifically, in the solvothermal synthesis experiment of S1 cadmium-naphthalimide-based photochromic material, it was found that the purity of the synthesized cadmium-naphthalimide-based photochromic material was the highest when the volume ratio of deionized water to N,N-dimethylformamide solution was 2:1.
[0027] Specifically, mixture A in S2 is reacted at a constant temperature of 90-110℃ for 2-4 days.
[0028] Specifically, in the S2 isothermal reaction experiment, multiple experiments verified that when mixture A reacted at 100℃ for 3 days, the cadmium-naphthalimide-based photochromic material obtained had the highest purity, fast light response speed, and long retention time.
[0029] Specifically, the optimal cooling rate of the synthesis reaction products in S2 is 4℃ / h.
[0030] Specifically, the cadmium-naphthalimide-based photochromic material obtained from S2 is used in the field of amine substance detection test strips, and its application process is as follows: T1. The obtained cadmium-naphthalimide-based photochromic material powder is uniformly dissolved in methanol and ethanol, and polystyrene sulfonic acid dispersant, polyethyleneimine binder and water are added to obtain a mixed solution; T2. Coat the mixed solution from step T1 evenly onto the filter paper, and after the surface is dried, obtain the rapid amine substance test strip.
[0031] Specifically, the optimal coating amount in step T2 is 50 mg / cm³. 2 .
[0032] The material preparation method of the present invention is applied in the following embodiments, specifically as follows: Example
[0033] S1. Dissolve Cd(NO3)2·4H2O (0.1mmol, 30.8mg), N,N'-bis(4-pyridimethylene)-1,4,5,8-naphthalenedimide (DPMNI, 0.05mmol, 22.4mg), and thiophene-2,5-dicarboxylic acid (H2TDC, 0.05mmol, 8.6mg) in 4ml of deionized water and 2ml of N,N-dimethylformamide solution, and dissolve by stirring. S2. The dissolved solution was placed in a high-pressure reactor with a 20ml polytetrafluoroethylene liner and the synthesis reaction was carried out by solvothermal method. The temperature was maintained at 100℃ in a constant temperature oven for 3 days, and then slowly cooled to room temperature at a rate of 4℃ / h. After washing with deionized water, orange-yellow blocky crystals were obtained, which is the target compound 1. The yield of the obtained cadmium-naphthalimide-based photochromic material was 87%, and its elemental analysis showed that C 32 H 18 The specific percentage of CdN4O8S is as follows: Theoretical values: C, 52.58; H, 2.48; N, 7.66%.
[0034] Experimental values: C, 52.17; H, 2.52; N, 7.45%.
[0035] The cadmium-naphthalimide-based photochromic materials were then characterized and their performance tested using the following instruments or methods: (1) X-ray crystallographic diffraction data: In Example 1, the single-crystal diffraction data of material compound 1 synthesized in step T2 were collected using a Bruker D8QUEST-Kα (λ=1.54178 Å) instrument. Reduction absorption correction was performed on the diffraction data. The crystal structure of the material compound was analyzed using the direct method, and refined using the F2 (SHELXL-2018) full-matrix least squares method. All non-hydrogen atoms in the crystal structure were anisotropically refined. Carbon atoms in the structure were theoretically hydrogenated, while nitrogen and oxygen atoms were manually hydrogenated. Disordered solvent molecules in the material compound structure could not be resolved and were processed using the "SQUEEZE" command in PLATON software to remove solvent molecules from the structure. The refined crystal parameters are shown in Table 1. Table 1 Crystal structure data of compound 1 Compound 1 Formula [C 32 H 18 CdN4O8S]]> Formula wt. 730.96 Cryst.syst Orthorhombic Space group a (Å) 23.259(4) b (Å) 10.2229(17) c (Å) 12.294(2) α (° ) 90 β (° ) 90 γ (° ) 90 V (A 3 )]]> 2923.3(8) Z 4 T (K) 292(2) Dc / g cm -3 ]]> 1.661 μ / mm -1 ]]> 7.181 F(000) 1464 Tot. Data 21624 Uniq. Data 1909 Rint 0.1088 GOF 0.829 [R1 [I>2σ(I)]]> 0.0594 wR2 (all data) 0.1866 Note: R 1=∑|| F o | - | F c || / ∑| F o |, wR 2={∑w[( F o ) 2 - ( F c ) 2 ] 2 / ∑w[( F o ) 2 ] 2} 1 / 2 ; Figure 1 The crystal structure diagrams of the materials in Example 1 of this invention are as follows: (a) is the structure diagram of N,N'-bis(4-pyridinylmethylene)-1,4,5,8-naphthalimide; (b) is the structure diagram of thiophene-2,5-dicarboxylic acid; (c) is the asymmetric unit of the cadmium-naphthalimide-based photochromic material; (d) is the coordination mode of the cadmium metal center in the cadmium-naphthalimide-based photochromic material. Figure 1 c) consists of a cadmium atom and a naphthalimide ligand ( Figure 1 Half of a), thiophene-2,5-dicarboxylic acid ligand ( Figure 1 In b), half of the nitrogen atom and one nitrogen atom are derived from the naphthalimide ligand, and the two oxygen atoms are derived from the thiophene-2,5-dicarboxylic acid ligand, as shown in the figure. Figure 1 As shown in d, the cadmium atom at the metal center has a six-coordinate octahedral geometry, with two nitrogen atoms derived from two different naphthalimide ligands and four oxygen atoms derived from two different thiophene-2,5-dicarboxylic acid ligands.
[0036] Figure 2 The crystal packing diagram of the material in Example 1 of the present invention shows that, due to the presence of nitrogen atoms and carboxylate ion coordination sites in the naphthalimide ligand and the thiophene-2,5-dicarboxylic acid ligand, which are connected to the cadmium atom at the metal center, and the intermolecular interactions, the structure of this material can form a three-dimensional network structure with pores.
[0037] (2) Conduct ultraviolet solid diffuse reflectance test: Figure 3The image shows the UV solid diffuse reflectance of the material in Example 1. The figure shows characteristic absorption peaks of conjugated aromatic compounds in the 200-400 nm range, and new absorption peaks appear in the 400-800 nm range. Specifically, three new strong absorption peaks are located at 618 nm, 701 nm and 783 nm, and the absorption intensity gradually increases with the extension of irradiation time (5 s, 10 s, 30 s, 1 min, 2 min, 3 min, 4 min).
[0038] (3) Powder X-ray diffraction test: Figure 4 The PXRD pattern of the material in Example 1 verifies that the material can recover the stability of its original color structure after discoloration under light and heating to 120°C. The figure shows that the powder X-ray diffraction (XRD) of the material after light and heating is consistent with the material simulation results, indicating that the material structure remains intact. This further proves that the discoloration response of the material is caused by the generation of free radicals, rather than by photoisomerization and photodecomposition. This result supports the potential application prospects of this compound in optical materials.
[0039] (4) Thermogravimetric analysis data: Figure 5 The figure shows the thermogravimetric (TG) curves of the material at temperatures ranging from 25°C to 800°C in air. Figure 5 The thermogravimetric curves of the material show a similar two-step weight loss occurring from room temperature to 656℃. The material experiences its first weight loss before 343℃, which can be attributed to the loss of lattice solvent molecules and counterions in the crystal. As the temperature increases, the second stage of weight loss occurs between 343℃ and 656℃, mainly due to the decomposition of the material's framework structure. Between 656℃ and 800℃, the material reaches a weight loss equilibrium, and its mass no longer changes, eventually forming cadmium oxide. Thermogravimetric analysis further demonstrates that the material has good thermal stability.
[0040] (5) Electron paramagnetic resonance spectral data: Figure 6 The ESR spectrum of the material shows a characteristic peak of DPMNI radical at 1.9987, which increases after photochromism, proving that the color change mechanism of the material is caused by photoinduced electron transfer (ET) of DPMNI radical. ERS detection further confirms that the color change of the material is caused by the generation of photoinduced radicals, completely ruling out the possibility of photoisomerization and photodecomposition of the material.
[0041] Example 2 S1. Dissolve Cd(NO3)2·4H2O (0.1mmol, 30.8mg), N,N'-bis(4-pyridimethylene)-1,4,5,8-naphthalenedimide (DPMNI, 0.05mmol, 22.4mg), and thiophene-2,5-dicarboxylic acid (H2TDC, 0.05mmol, 8.6mg) in 4ml of deionized water and 2ml of N,N-dimethylformamide solution, and dissolve by stirring. S2. The dissolved solution was placed in a reaction vessel with a 20 ml polytetrafluoroethylene liner and synthesized by solvothermal method. The temperature was maintained at 90℃ in a constant temperature oven for 3 days. Then, it was slowly cooled to room temperature at a rate of 4℃ / h. After washing with deionized water, orange-yellow blocky crystals were obtained, which is the target compound 1. Its material yield was 75%, but the purity was not high and there were impurities.
[0042] Example 3 S1. Dissolve Cd(NO3)2·4H2O (0.1mmol, 30.8mg), N,N'-bis(4-pyridinylmethylene)-1,4,5,8-naphthyldiimide (DPMNI, 0.05mmol, 22.4mg), and thiophene-2,5-dicarboxylic acid (H2TDC, 0.05mmol, 8.6mg) in 4ml of deionized water and 2ml of N,N-dimethylformamide solution, and dissolve by stirring. S2. The dissolved solution was placed in a reaction vessel with a 20 ml polytetrafluoroethylene liner and synthesized by solvothermal method. The temperature was maintained at 110℃ in a constant temperature oven for 3 days. Then, it was slowly cooled to room temperature at a rate of 4℃ / h. After washing with deionized water, orange-yellow blocky crystals were obtained, which is the target compound 1. The material yield was 72%, and the purity was not high and there were impurities.
[0043] Example 4 S1. Dissolve Cd(NO3)2·4H2O (0.1mmol, 30.8mg), N,N'-bis(4-pyridinylmethylene)-1,4,5,8-naphthyldiimide (DPMNI, 0.05mmol, 22.4mg), and thiophene-2,5-dicarboxylic acid (H2TDC, 0.05mmol, 8.6mg) in 4ml of deionized water and 2ml of N,N-dimethylformamide solution, and dissolve by stirring. S2. The dissolved solution was placed in a reaction vessel with a 20ml polytetrafluoroethylene liner and synthesized by solvothermal method. The temperature was maintained at 100℃ in a constant temperature oven for 3 days. Then, it was slowly cooled to room temperature at a rate of 4℃ / h. After washing with deionized water, orange-yellow blocky crystals were obtained, which is the target compound 1. The material yield was 70%, and the purity was not high and there were impurities.
[0044] Example 5 S1. Dissolve Cd(NO3)2·4H2O (0.1mmol, 30.8mg), N,N'-bis(4-pyridimethylene)-1,4,5,8-naphthyldiimide (DPMNI, 0.05mmol, 22.4mg), and thiophene-2,5-dicarboxylic acid (H2TDC, 0.05mmol, 8.6mg) in 3ml of deionized water and 3ml of N,N-dimethylformamide solution, and dissolve by stirring. S2. The dissolved solution was placed in a reaction vessel with a 20ml polytetrafluoroethylene liner and synthesized by solvothermal method. The temperature was maintained at 100℃ for 3 days in a constant temperature oven. Then, it was slowly cooled to room temperature at a rate of 4℃ / h. After washing with deionized water, orange-yellow blocky crystals were obtained, which is the target compound 1. The material yield was 78%, and the purity was not high and there were impurities.
[0045] Example 6 S1. Dissolve Cd(NO3)2·4H2O (0.1mmol, 30.8mg), N,N'-bis(4-pyridimethylene)-1,4,5,8-naphthalenedimide (DPMNI, 0.05mmol, 22.4mg), and thiophene-2,5-dicarboxylic acid (H2TDC, 0.05mmol, 8.6mg) in 3ml of deionized water and 1ml of N,N-dimethylformamide solution, and dissolve by stirring. S2. The dissolved solution was placed in a reaction vessel with a 20 ml polytetrafluoroethylene liner and synthesized by solvothermal method. The temperature was maintained at 100℃ in a constant temperature oven for 3 days. Then, it was slowly cooled to room temperature at a rate of 4℃ / h. After washing with deionized water, orange-yellow blocky crystals were obtained, which is the target compound 1. The material yield was 74%, and the purity was not high and there were impurities.
[0046] Example 7 S1. Dissolve Cd(NO3)2·4H2O (0.1mmol, 30.8mg), N,N'-bis(4-pyridimethylene)-1,4,5,8-naphthalenedimide (DPMNI, 0.05mmol, 22.4mg), and thiophene-2,5-dicarboxylic acid (H2TDC, 0.05mmol, 8.6mg) in 3ml of deionized water and 1ml of N,N-dimethylformamide solution, and dissolve by stirring. S2. The dissolved solution was placed in a reaction vessel with a 20 ml polytetrafluoroethylene liner and synthesized by solvothermal method. The temperature was maintained at 100℃ in a constant temperature oven for 3 days. Then, it was slowly cooled to room temperature at a rate of 4℃ / h. After washing with deionized water, orange-yellow blocky crystals were obtained, which is the target compound 1. The material yield was 79%, and the purity was not high and there were impurities.
[0047] The following experimental tests were conducted on the material of Example 1 prepared by the method of the present invention: Experimental Example 1 Photochromic experiment: The material prepared in Example 1 was irradiated with a 300W xenon lamp. The color changed significantly over time, exhibiting extremely fast light response; it changed from orange-yellow to brownish-yellow within 5 seconds, and reached saturation, turning dark brown, within 2 minutes. The material was very stable after irradiation; it did not revert to its original color after being placed in the dark for 30 days. However, when the irradiated material was heated at 120°C for 1 hour, it regained its original color. Figure 7 As shown.
[0048] Experiment Example 2 Adsorption and color change experiment of amine substances: The selected amine substances were ammonia, n-propylamine, n-butylamine, dimethylamine, and triethylamine. The adsorption and color change experiment of amine substances was carried out in beakers under slight heating and evaporation conditions, with a concentration of 150 mg / m³. 3 The colors are brownish-yellow, light brown, brown, dark brown, dark tan, and reddish-brown, respectively. Photos of the material prepared in Example 1 before and after color change are shown below. Figure 8 As shown.
[0049] Experimental Example 3 Amine substance test strip test: (1) Take 0.1g of the cadmium-naphthalimide-based photochromic material prepared in Example 1, dissolve it with 3ml of methanol and 3ml of ethanol, then add it to a mixed solution of 3g of polystyrene sulfonic acid, 3g of polyethyleneimine and 3ml of water, stir well, and evenly coat the mixture onto a filter paper disc three times, with a total coating amount of 50mg / cm. 2 Test strips are dried to obtain rapid ammonia detection test strips.
[0050] (2) Dissolve five amines—ammonia, n-propylamine, n-butylamine, dimethylamine, and triethylamine—in ethanol to prepare a quantitative solution. Inject this solution into a sealed container of known volume using a quantitative syringe. Heat the solution until it is completely vaporized. The ammonia concentration in the container is 15 mg / L. Place the amine test paper prepared in step S1 into the container. After 5 seconds, the paper will change color. The result is as follows: Figure 9 As shown, the filter paper turns brownish-yellow, light brown, brown, dark brown, dark brown, and reddish-brown respectively in an amine atmosphere. The test paper can return to its original color in about 3 to 5 minutes after leaving the amine environment. The color change is reversible and can be reused multiple times.
[0051] Experiment Example 4 Adsorption-induced color change of amines in ultraviolet diffuse reflectance of solids: Figure 10The image shows the UV diffuse reflectance of the material prepared in Example 1, which exhibits a slight change in color due to the adsorption of amines. As can be seen from the image, the change ranges from 60 to 800 nm, indicating that intermolecular electron transfer occurred between the amine and the free radical of the DPMNI ligand.
[0052] Experimental Example 5 X-ray powder diffraction of amines: Figure 11 The PXRD patterns of the material prepared in Example 1 exposed to different amine environments are shown in the figure. The main peaks of the powder XRD show that there is almost no change, which indicates that the material prepared in Example 1 has excellent chemical stability.
[0053] Attached image description: Figure 1 The diagram shows the crystal structure of the material in Example 1 of this invention. In the diagram, (a) is the structure of N,N'-bis(4-pyridimethylene)-1,4,5,8-naphthalimide, (b) is the structure of thiophene-2,5-dicarboxylic acid, (c) is the asymmetric unit of the cadmium-naphthalimide-based photochromic material, and (d) is the coordination mode of the cadmium metal center in the cadmium-naphthalimide-based photochromic material.
[0054] In summary, the cadmium-naphthalimide-based photochromic material prepared in this invention combines photoinduced free radical generation characteristics with a stable three-dimensional network structure, exhibiting rapid and reversible photochromic properties. It can achieve highly sensitive detection of various amines through significant color changes. The preparation process features high product purity and excellent material properties. When applied to test strips, the resulting material demonstrates advantages such as rapid response, strong selectivity, and reusability, showing promising application prospects in the fields of optical information storage and rapid detection of amines.
[0055] Although embodiments of the invention have been shown and described, it will be understood by those skilled in the art that various changes, modifications, substitutions and alterations can be made to these embodiments without departing from the principles and spirit of the invention, the scope of which is defined by the appended claims and their equivalents.
Claims
1. A method for producing a cadmium-naphthalene dicarboximide-based photochromic material, characterized by, The method comprises the following steps: S1, dissolving cadmium salt, naphthalimide ligand (N, N'-di(4-pyridylmethylene)-1, 4, 5, 8-naphthalimide) and thiophene-2, 5-dicarboxylic acid ligand in a mixed solvent of deionized water and N, N-dimethylformamide according to a set molar ratio, and dissolving by stirring to obtain mixture A; S2, placing the dissolved mixture A in a reaction kettle with a polytetrafluoroethylene lining, and performing a synthesis reaction by a solvothermal method; after the reaction is completed, cooling to room temperature at a rate of 3.5-4.0 ℃ / h, washing with deionized water for 3-5 times until the supernatant is colorless and neutral, and finally obtaining orange-yellow block crystals, which are cadmium-naphthalimide-based photochromic materials; S3, preparation of amine substance detection test paper: taking filter paper as the bottom layer, mixing the cadmium-naphthalimide-based photochromic material, a dispersing agent and a binder in sequence, and suction-filtering onto the filter paper to obtain the amine substance detection test paper.
2. The method for preparing a cadmium-naphthalimide-based photochromic material according to claim 1, characterized in that: In the step S1, the set molar ratio of the cadmium salt and the naphthalimide ligand (N, N'-di(4-pyridylmethylene)-1, 4, 5, 8-naphthalimide) to the thiophene-2, 5-dicarboxylic acid ligand is (1-2):1:1; and the cadmium salt is selected from any one of cadmium nitrate, cadmium chloride or cadmium bromide.
3. The method for preparing a cadmium-naphthalimide-based photochromic material according to claim 1, characterized in that: In the step S1, the volume ratio of the deionized water to the N, N-dimethylformamide is (1-4):
1.
4. The method for preparing a cadmium-naphthalimide-based photochromic material according to claim 1, characterized in that: In the step S1, the specific process for obtaining the mixture A is: stirring at room temperature and a stirring speed of 700-800 rpm for 2-3 hours, and then filtering through a 0.22 μm organic filter membrane to obtain the mixture A.
5. The method for preparing a cadmium-naphthalimide-based photochromic material according to claim 1, characterized in that: In the step S2, the synthesis reaction conditions are: constant temperature at 90-110 ℃ for 2-4 days.
6. The method of claim 1, wherein the cadmium-naphthalene diimide-based photochromic material is prepared by the following steps: (1) synthesizing a naphthalene diimide compound; (2) synthesizing a cadmium compound; and (3) mixing the naphthalene diimide compound and the cadmium compound. In the step S3, the preparation of the amine substance detection test paper: taking filter paper as the bottom layer, mixing the cadmium-naphthalimide-based photochromic material prepared in S2, a dispersing agent and a binder in a mixed solvent of methanol and ethanol in a certain proportion to form a uniform mixed solution, and then suction-filtering the mixed solution onto the filter paper, with a loading amount controlled at 49.5-50.5 mg / cm2, and then air-drying to obtain the amine substance detection test paper.
7. The method of claim 1, wherein the cadmium-naphthalene diimide-based photochromic material is prepared by the following steps: (1) synthesizing a naphthalene diimide compound; (2) synthesizing a cadmium compound; and (3) mixing the naphthalene diimide compound and the cadmium compound. The photochromic material has the structural formula [Cd(DPMNI)(H2TDC)]. n Its molecular formula is C 32 H 18 CdN4O8S; wherein, DPMNI is a naphthalimide ligand (N,N'-bis(4-pyridimethylene)-1,4,5,8-naphthalimide), and H2TDC is a thiophene-2,5-dicarboxylic acid ligand; The asymmetric unit comprises one metal cadmium atom, one half of the naphthalimide ligand, one half of the thiophene-2, 5-dicarboxylic acid ligand, one nitrogen atom derived from the naphthalimide ligand and two oxygen atoms derived from the thiophene-2, 5-dicarboxylic acid ligand; The metal central cadmium atom is in an octahedral geometry with six coordination sites, two nitrogen atoms derived from two different naphthalimide ligands and four oxygen atoms derived from two different thiophene-2, 5-dicarboxylic acid ligands; due to the presence of the nitrogen atoms and carboxylate ion coordination sites in the naphthalimide ligand and the thiophene-2, 5-dicarboxylic acid ligand, which are connected to the metal central cadmium atom, and the intermolecular interaction, the structure of the material can form a three-dimensional network structure with pores.
8. The method of claim 7, wherein the cadmium-naphthalene diimide-based photochromic material is prepared by the following steps: (1) synthesizing a naphthalene diimide compound; (2) synthesizing a cadmium compound; and (3) mixing the naphthalene diimide compound and the cadmium compound. The photochromic material crystallizes in the orthorhombic space group Pnma with unit cell parameters a = 23.259(4) A, b = 10.2229(17) A, c = 12.294(2) A, α = 90°, β = 90°, The photochromic material changes color from orange-yellow to brown under light irradiation for 5-6 seconds, and can restore the original color under heating at 118-120 ℃ for 1-1.1 h, and the color changing process is reversible. = 90°, V = 2923.3(8) A 3 , Z = 4.
9. The method of claim 1, wherein the cadmium-naphthalene diimide-based photochromic material is prepared by the following steps: (1) synthesizing a naphthalene diimide compound; (2) synthesizing a cadmium compound; and (3) mixing the naphthalene diimide compound and the cadmium compound. 10. The method for preparing a cadmium-naphthalimide-based photochromic material according to claim 1, characterized in that: The photochromic material is applied to the field of amine substance detection test paper.